Coupling Cas9 to artificial inhibitory domains enhances CRISPR-Cas9 target specificity - Aschenbrenner, Sabine; Kallenberger, Stefan M.; Hoffmann, Mareike; Huck, Adrian; Eils, Roland; Niopek, Dominik (Science advances, 2020)
The limited target specificity of CRISPR-Cas nucleases poses a challenge with respect to their application in research and therapy. Here, we present a simple and original strategy to enhance the specificity of CRISPR-Cas9 genome editing by coupling Cas9 to artificial inhibitory domains. Applying a combination of mathematical modeling and experiments, we first determined how CRISPR-Cas9 activity profiles relate to Cas9 specificity. We then used artificially weakened anti-CRISPR (Acr) proteins either coexpressed with or directly fused to Cas9 to fine-tune its activity toward selected levels, thereby achieving an effective kinetic insulation of ON- and OFF-target editing events. We demonstrate highly specific genome editing in mammalian cells using diverse single-guide RNAs prone to potent OFF-targeting. Last, we show that our strategy is compatible with different modes of delivery, including transient transfection and adeno-associated viral vectors. Together, we provide a highly versatile approach to reduce CRISPR-Cas OFF-target effects via kinetic insulation. - Fusing attenuated anti-CRISPR proteins to Cas9 improves specificity via kinetic insulation of ON- and OFF-target editing events. - Fusing attenuated anti-CRISPR proteins to Cas9 improves specificity via kinetic insulation of ON- and OFF-target editing events.
Gesehen am 30.03.2020